Respostas
respondido por:
23
13 = 13
39 = 3 * 13
52 = 2² * 13
mmc 13 * 2² * 3 =156
mdc = 13
39 = 3 * 13
52 = 2² * 13
mmc 13 * 2² * 3 =156
mdc = 13
respondido por:
7
Olá!
mmc=13 =13
mmc=39/ 13
---------3 / 3
mmc=52 / 2
--------26 / 2
--------13 / 13
mmc= 2 × 2 ×3 × 13 = 156
mdc= 13
Espero ter ajudado!
mmc=13 =13
mmc=39/ 13
---------3 / 3
mmc=52 / 2
--------26 / 2
--------13 / 13
mmc= 2 × 2 ×3 × 13 = 156
mdc= 13
Espero ter ajudado!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás